OFW coverage in broadcast media a case study of "Byaheng Langit" - Varona, Karen Y. (2010)
This paper examines OFW coverage in the longest running OFW-oriented program on AM Radio, "Byaheng Langit," as well as its counterpart and namesake on TV. Specifically, the study answers the following questions: What OFW issues are tackled in the program? Is there an attempt to delve into OFW issues? What other issues need to be explored? The study finds that "Byaheng Langit" coverage is generally lacking in content and relevance. After more than twenty years, the program still mainly dedicates itself to "bridging the gap" when this has ceased to be a problem with the advent of cellular phones and the internet. Also, since the program mostly focuses on free calls, content is severely limited into greetings, sending/receiving remittances/packages, requests for help to work abroad, and requests to buy something. The challenge for "Byaheng Langit," and media, in general, is to put migration stories in context to enable Filipino audiences to better understand the phenomenon and to better reflect on whether it was good or bad. Issues suggested include the social costs of migration, return and reintegration, economic issues, labor export policies, and health/social issues.
Keywords: Filipino foreign workers; Digital multimedia broadcasting; Byaheng Langit (Radio program)